The Validation of a Single Multiplex Typing System With 45 Y-STR Markers for Familial Searching and Database Construction - Zeng, Ying; Chen, Ling; Wang, Mengge; Yang, Chengliang; Liu, Hong; Xiao, Cheng; Liu, ChangHui; Li, Yue; Xu, Quyi; Du, Weian; Liu, Chao (Frontiers in Genetics, 2022)
Y-chromosomal short tandem repeat (Y-STR) is an effective forensic tool in familial searches and patrilineal relationship evaluation. However, currently available Y-STR panels often lack sufficient discriminatory power to resolve genetic relationships between distant relatives or within patrilocal populations. This study aims to establish a novel Y-STR amplification system for forensic casework analysis and database construction, which contains forty-four slowly and moderately and one rapidly mutating Y-STRs. The validation of the assay was conducted following the recommendations of SWGDAM developmental validation guidelines. Different types of casework samples were tested and reliable profiles were obtained. Furthermore, we genotyped and analyzed 141 unrelated Han Chinese male samples. The results showed that this Y45 kit could improve the performance of identifying male individuals, higher haplotype diversity and discrimination capacity were observed when compared to the previously widely used Yfiler Plus kit. In general, the validation study demonstrated that the newly developed Y45 kit possesses high sensitivity, inhibitor tolerance, male-specificity in a mixture, species specificity, precision, and is capable of forensic casework analysis and database construction.